Translational control of Scamper expression via a cell-specific internal ribosome entry site - De Pietri Tonelli, Davide (Oxford University Press, 2003)
The mRNA of Scamper, a putative intracellular calcium channel activated by sphingosylphosphocholine, contains a long 5′ transcript leader with several upstream AUGs. In this work we have investigated the role this sequence plays in the translational control of Scamper expression. The cytosolic transcription machinery of a T7 RNA polymerase recombinant vaccinia virus was used to avoid artifacts arising from cryptic promoters or mRNA processing. Based on transient transfection experiments of dicistronic and bi-monocistronic plasmids expressing reporter genes, we present evidence that the 5′ transcript leader of Scamper contains a functional internal ribosome entry site (IRES). Our data indicate that Scamper translation in Madin-Darby canine kidney cells is driven by a cap-independent mechanism supported by the IRES activity of its mRNA. Finally, the Scamper IRES appears to be the first IRES with specificity for kidney epithelial cells.